P-461: Blood pressure and catecholamines in uygur centenarian in Xinjian, China - Mitsubayashi, Hiromi; Kawamura, Hiroshi; Ozawa, Yukio; Izumi, Yoichi; Jumabay, Medet; Zhang, Xiangyang; Yassen, Mammet (American journal of hypertension, 2004)
Recent studies have indicated that many factors attribute to the longevity of human life. However, blood pressure patterns and sympathoadrenal activities are not well known in longevity. The purpose of this study was to clarify the relationship between blood pressure variation and urinary catecholamines in centenarian people. We investigated 236 elderly subjects in Uygurs in Hotan, Xinjiang region. Subjects were divided into three groups: 1. Centenarian group (33 subjects, age≥100 yr.); 2. Longevous group (103 subjects, aged 90∼100 yr.); 3. Elderly group (100 subjects, aged 65∼70 yr.). Blood pressure (BP) and pulse rate (PR) were monitored every 30 min for 26 hours using ambulatory blood pressure monitoring (ABPM) method. Office and mean 24 hr BP, PR were analyzed in each group with conventional statistics. Urinary catecholamines were measured with HPLC-DPE methods. Mean 24-hr BP was higher in centenarian group than in other two groups (p<0.05). The differences between daytime BP and nighttime BP was smaller in centenarian group than in other two groups (p<0.001). Ratio of dipper was 21.1% in centenarian group, 32% in longevous group and 36.4 % in elderly groups, respectively. Circadian variation of BP was more variable and the profile of hourly variation tended to be flat in the centenarian group. However, the profiles of circadian rhythm of BP in longevous and elderly groups have shown morning rising and nocturnal dipping. Urinary norepinephrine concentrations(NE) was not different among the three groups. However, urinary epinephrine concentrations(E) in centenarian group higher than the other two groups. Sympathoadrenal activities may attribute to higher BP in centenarian, The variation of BP may decrease with advanced aging. Am J Hypertens (2004) 17, 202A–202A; doi: 10.1016/j.amjhyper.2004.03.535